The effect of nanofilled resin coating on the hardness of glass ionomer cement - Michael William Handoko; Rosalina Tjandrawinata; Octarina (Wolters Kluwer Medknow Publications, 2020)
Background: Glass ionomer cement (GIC), a dental material that is constantly being developed and improved, is a biocompatible restorative material with physical, mechanical, and chemical properties that resemble teeth. This material is often used in dentistry because it can release fluoride. However, it has low wear resistance and is very sensitive to moisture, which can reduce the hardness. Objectives: The aim of this research is to evaluate the influence of applying nano-filled resin coatings on GIC to increase the hardness, especially after 24 h. Methods: This research is a pre-posttest laboratory experiment with a control group design. In this study, GIC Type II (EQUIA Forte® Fil, GC, Japan) was mechanically manipulated and inserted into molds to produce twenty samples of 6.0 ± 0.3 mm in diameter and 3.0 ± 0.2 mm in height. The GIC samples were divided into two groups: ten samples that were not coated with nano-filled resin formed the control group, while the other ten samples that were coated with nano-filled resin (EQUIA Forte Coat, GC, Japan) were the treatment group. The GIC samples were tested immediately using the Vickers hardness (VHN) test and then immersed in sterile distilled water in a 37°C incubator. After 24 h, the GIC samples were tested for their final hardness value. Results: The group that received the coating had a greater hardness value (131.14 ± 36.15 VHN) that was statistically significantly higher (t-test, P < 0.05) than that of the group with no coating (13.56 ± 4.28 VHN). Conclusion: Nano-filled resin coating applications on GIC significantly increase the hardness after 24 h.